Breakdown - Mostow, Jonathan; Russell, Kurt.; Walsh, J. T.; Quinlan, Kathleen, 1954-; Paramount Pictures Corporation (Hollywood, CA : Paramount, 1998)
A man searches for his missing wife after his car breaks down in the middle of the desert.
Originally released as motion picture.
For specific features see interactive menu.
Kurt Russell, J.T. Walsh, Kathleen Quinlan.
DVD.
Keywords: Missing persons -- Southwest, New; Trucker drivers; Conspiracy; Personas desaparecidas -- Suroeste, Nuevo; Asociacion delictuosa; Feature films; Adventure films; Video recordings for the hearing impaired